(untitled) (Research, Society and Development, 2021)
Lymphoma is a disorder of the hematopoietic system whose etiology involves a disordered proliferation of lymphoid cells, in which multicentric lymphoma is triggered by generalized lymph node enlargement. The Madison-Wisconsin protocol is one of the most used polychemotherapies in the treatment of multicenter lymphomas in dogs, being verified by the drugs cyclophosphamide, doxorubicin, vincristine and prednisone, and administered alternately over 19 weeks. This study aimed to report the efficiency of the Madison-Wisconsin therapeutic protocol in the total remission of a multicentric lymphoma in a dog. The animal assisted was a French Bulldog breed dog, which presented enlargement of the submandibular, pre-scapular, axillary, inguinal and popliteal lymph nodes and, on physical examination, the enlargement in the mesogastric region suggested splenomegaly. Cytological examination of the submandibular and popliteal lymph nodes was compatible with lymphoma. Ultrasonographic examination detected a marked increase in the spleen and liver, characterizing hepatosplenomegaly. No Doppler echocardiogram was possible to observe an increase in the left atrium. There was hematological follow-up of the patient during chemotherapy treatment and throughout the therapeutic course or changes in animals in the blood count, such as thrombocytosis and neutropenia, which required additional treatment. Without biochemical examination, there was an increase in ALT. After the end of chemotherapy, the animal presented complete remission of the neoplasm, demonstrating the therapeutic success of the Madison-Wisconsin protocol on lymphoma.